Tuberculous abdominal abscess in an HIV-infected man: Neither infection previously diagnosed - Kuo-Yao Kao; Tsung-I Hung (AOSIS, 2010)
A 38-year-old man had a 1-week history of right lower quadrant abdominal pain; the initial impression was that he had diverticulitis of the ascending colon with an intra-abdominal abscess. Signs of peritonitis mandated an immediate right hemicolectomy. The unusual location of the abscess and the patient's unusual postoperative course suggested that he might also have a systemic disease. Testing for HIV infection was positive. After 2 weeks in hospital, he was treated as an outpatient for both tuberculosis and HIV with a favourable outcome. In Taiwan a pre-operative HIV test is not performed routinely, and the HIV seroprevalence in surgical patient populations is unknown. Surgeons should keep the possibility of HIV infection in mind in a patient with an unusual clinical course.